Fabrication of Beads and Biofilms Based on Alginate with Iron (III) Oxide, Titanium (IV) Oxide and Copper (II) Oxide - IDRIS, MAIZLINDA IZWANA; Mohd Nasir, Nur Fatehah (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Natural alginate is a polysaccharide that can be found in seaweed. As a result of its widespread use in biomedical applications such as wound dressing, tissue regeneration, blood vessel and drug delivery, alginate is also known as a non-toxic substance that is biodegradable, biocompatible, biodegradable, and hydrophilic. Materials that were used along with alginate were Iron (III) Oxide, Titanium (IV) Oxide, and Copper (II) Oxide. Because of its many benefits in the field of biomedical application, including being used as an MRI contrast agent, controlled drug release, biocompatibility, and resistance to corrosion. For the purpose of this study, Alginate at a 1 wt.% was combined homogenously with Iron (III) Oxide, Titanium (IV) Oxide, and Copper (II) Oxide at respective weights of 0.1g, 0.2g, and 0.3g in order to fabricate films and bead. Beads were produced using a syringe method, which involved pressing the syringe into a beaker containing calcium chloride, whereas films were produced using a casting method. The morphology and physicochemical properties of Alginate doped with Iron (III) Oxide, Titanium (IV) Oxide, and Copper (II) Oxide were the primary objective of this research project. In order to complete this research project, the following characterization and testing methods were utilised: Scanning Electron Microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), and last but not least, contact angle measurement. SEM images showed that some samples have microstructure and wavy surface. EDX result from SEM shows that the elements for Iron (III) Oxide, Titanium (IV) Oxide and Copper (II) Oxide along with alginate and calcium chloride were present. According to the findings of XRD, the intensity of the elements in a sample increases proportionally with the number of distinct element compositions present in the sample. The FTIR results for films each elements showed consistent results. Every contact angle is less than 90°, which indicates that the surfaces are hydrophilic and wettable. It is possible to draw the conclusion that Alginate that contains Iron (III) Oxide, Titanium (IV) Oxide, and Copper (II) Oxide will benefit in the future.